INTERNATIONAL LAW AND ITS CHALLENGES IN THE RUSSIA- UKRAINE WAR - N. N. Ike, Cyriacus; Chinedu U. Udumaga, Cornel; N. Osudibia, Ngozi (African Journal of Social and Behavioural Sciences, 2024)
The ongoing war between Russia and Ukraine is challenging international relations, with the unmitigated destruction of lives and billions of dollars in national asserts on both sides. What is more worrisome in the crisis, is that scholars in the field are bereft of any logical explanation to the stand of international law as an instrument of taming unilateral actions of states and the rascality. This study raises pertinent research questions: Does international law live up to its biddings? Does it still regulate the conduct of state and nonstate actors in the international system? Why has Russia damned and taken the law for worthless documentation, as it continues to obdurate its atrocious invasion of Ukraine? Is the international system helpless, or how does it extricate itself from this rumble? The work used a secondary qualitative method for data collection, and to interrogate the stand of Russia and the position of international law in the war, the work utilised a compound analysis of realism state-centred theory, offensive realism and protracted social conflict (PSC) theory. Findings show that Russia‘s claim of self-defence and humanitarian interventions are mere pretentious deceit without moral or legal logic. The scenario seems to show that international law a mere document of moral jurisdiction impinging on the UN an irredeemable limitation. This study concludes that international law is weak, as the umbrella body of interstate relations- the UN has an inherent weakness as it lacks sufficient legal mandate for enforce sanctions on sovereign states actions that violates its laws. The paper suggests that the way to curb further free-for-all violations of international law and the kind of carnage going on in the war between Russia and Ukraine is, to give the UN stronger legal mandate to enforce its laws on deviant states.